PRODUÇÃO, CARACTERIZAÇÃO, CITO E GENOTOXICIDADE DE NANOESTRUTURAS CONTENDO ÓLEO DE GERÂNIO E AVALIAÇÃO DO SINERGISMO SOBRE LISTERIA MONOCYTOGENES FRENTE A ÓLEOS ESSENCIAIS - Fausto, Viviane Pedroso (2017)
Listeria monocytogenes is a food-borne bacterium that causes an infection called listeriosis, Although rare, this infection can be lethal for immunocompromised, pregnant, and stillborn. The objective of this work was to develop, characterize, evaluate the stability, anti-Listeria monocytogenes activity, cytotoxicity and genotoxicity of nanostructures (nanocapsules and nanoemulsion) containing Geranium essential oil (OEG), as well as verify synergistic effects with the essential oils of Cinnamon, Lemongrass And Thyme. The characterization of the essential oils was performed by GCMS. The nanocapsules (NC) were prepared by the interfacial deposition method of the preformed polymer while Geranium nanoemulsion (NEG) was prepared by homogenization using an Ultra-Turrax T18. The analysis of the stability indicators was performed by the evaluation of particle size, polydispersity index, zeta potential and pH for 60 days. The bactericidal effect of the different concentrations of the essential oils, pure or in combination and the synergism were determined by the serial microdilution technique, the cytotoxicity was determined by the MTT assays and determination of the LDH in VERO cells and the genotoxicity was evaluated by the GEMO test. Results: The NCGs produced had mean nanometer diameters of (232.6 nm), polydispersity indices below 0.053, pH 3.5 and zeta potentials of about -20.7 mV. The study demonstrated that the stability of the formulations is temperature dependent, remaining more stable at refrigeration temperatures (4 °C) or at stable temperatures (25 ° C). The NEG had mean nanometer diameters of (136.2.6 nm), polydispersity indices below 0.039, pH 3.4 and zeta potentials of about -8.1 mV. The MICs obtained for Geranium, Cinnamon, Campi-lemon and Thyme oils were 10975 mg / ml, 0.05 mg / ml, 0.18 mg / ml and 0.35 mg / ml, respectively. The CIM of NEG was 0.0625 mg / ml and the nanocapsules did not demonstrate antimicrobial activity in the test performed. It was possible to observe at least one point of synergism between the OE of geraniums and the tested EOs.the nanostructures did not show synergistic effect with OE. In the MTT assay OEG and NEG showed increased cell viability at concentrations of 10, 100 and 1000 μg / μl as compared to the control, the LDH assay shows that both OEG and NEG at concentrations of 0,1, 1, 10, 100 and 1000 μg / μl were not cytotoxic. In the GEMO test the OEG had a genoprotective effect on lymphocytes at concentrations of 10, 100 and 1000 μg / μl. The study demonstrated that both OG and NEG do not present tocicity 7 and genotoxicity but present very high MIC values to be used in food, and the synergism and nanostructuring were a good alternative to reduce the amount of oil required for an antimicrobial response.